A constraint programming model with time uncertainty for cooperative flight departures - Schefers, Nina; Ramos González, Juan José; Folch, Pau; Munoz-Gamarra, José Luis (Transportation research. Part C, Emerging technologies, 2018)
[Display omitted] •New departure synchronization mechanism to reduce probability of ATC interventions.•Mitigation mechanism based on Constraint Programming.•Air space digitalization to support TBO.•Methodology considers the downstream effects of the applicable mitigation measures.•Demonstration of methodology benefits in realistic traffic scenarios. The lack of a proper integration of strategic Air Traffic Management decision support tools with tactical Air Traffic Control interventions usually generates a negative impact on the Reference Business Trajectory adherence, and in consequence affects the potential of the Trajectory-Based Operations framework. In this paper, a new mechanism relaying on Reference Business Trajectories as a source of data to reduce the amount of Air Traffic Controller interventions at the tactical level while preserving Air Traffic Flow Management planned operations is presented. Artificial Intelligence can enable Constraint Programming as it is a powerful paradigm for solving complex, combinatorial search problems. The proposed methodology takes advantage of Constraint Programming and fosters adherence of Airspace User’s trajectory preferences by identifying tight interdependencies between trajectories and introducing a new mechanism to improve the aircraft separation at concurrence events considering time uncertainty. The underlying philosophy is to capitalize present degrees of freedom between layered Air Traffic Management planning tools, when sequencing departures at the airports by considering the benefits of small time stamp changes in the assigned Calculated Take-Off Time departures and to enhance Trajectory-Based Operations concepts.